Status of Parcel Fragmentation in Nepal (Journal on Geoinformatics, Nepal, 2022)
transfer, mortgage their own land. Parcel fragmentation is the division of a parcel into two or more parcels. This research was carried out to analyse the current status of parcel fragmentation in Nepal. According to the findings of this research, parcel fragmentation in Nepal is haphazard mainly focussing on urban and peri urban arears consequently parcel being irregular in shape & smaller in size and ultimately incrementing huge number of land owners with in fixed area. In the context of Nepal, factors that drive parcel fragmentation are cultural, social, legal, economical, frequent disasters, geographic variations, unmanaged migrations, haphazard land use planning amongst others. The uncontrolled and unmanaged parcel fragmentation in Nepal is the major challenge for land use planning and its implementation. Dense parcel fragmentation has created land related disputes. it is recommended that the government should reformulate and implement the proper land use policy as well as its supporting acts that encourage landconsolidation in agricultural zone and reducing haphazard parcel fragmentation in urban and peri urban areas.